Experimental studies on the effects of green space and evapotranspiration on urban heat island in a subtropical megacity in China. (October 2017) - Qiu, Guo Yu; Zou, Zhendong; Li, Xiangze; Li, Hongyong; Guo, Qiuping; Yan, Chunhua; Tan, Shenglin
Abstract: Urbanization is one of the most important driving forces of global change. With the quick expansion of the urban environment's size and population, its urban heat island intensity (UHII, expressed as the temperature difference between urban and rural areas) has rapidly increased. The situation is even worse in megacities, whose populations are greater than 10 million. However, very few studies quantitatively reveal the effects of green space and land use/land cover (LULC) on the urban thermal environment because they lack detailed measurements. This study focuses on quantifying the effects of green space on the urban heat island (UHI) in Shenzhen, a subtropical megacity in China. Extensive measurements (air temperature and humidity) were taken using a mobile traverse method in an 8 km long transect, where a variety of LULC types were included. Measurements were conducted at 2-h intervals for 2 years (repeated a total of 7011 times). The relationship between evapotranspiration (ET) and UHII was also studied based on measured data, to understand the mechanism of the cooling effect of vegetation. The main conclusions obtained are as follows: (1) There are obvious differences in the air temperature and UHII among different urban landscapes. The ranking of temperatures from highest to lowest is commercial area > urban village > urban water body > urban green space > suburb. The difference in the UHII is also obvious, especially from 20:00 PM to 06:00 AM, when the UHII is usually greater than 2 °C. (2) Green space and water bodies in the urban environment have obvious effects on reducing the air temperature through evapotranspiration. The cooling effect of urban green spaces is better than that of urban water bodies. Compared to commercial areas, urban water bodies can relieve the UHII up to 0.9 °C, whereas urban green spaces can relieve the UHII up to 1.57 °C. (3) There are obvious linear relationships between air temperature, UHII, and green space in nighttime. Air temperature and the UHII decrease linearly with an increase in urban green space. The correlation is relatively weak in daytime, when the cooling effect of vegetation might be offset by other factors in urban thermal environment. (4) Obvious correlation between ET and UHII was observed and a good positive linear relationship between ET and the decreasing rate of UHII (UHII′) was obtained, revealing that the faster ET is, the better UHII mitigating efficiency could be gained. An ET rate of 6.12 mm d −1 could cause a 0.12 °C per hour decrease in UHII under our experimental condition. These results indicate that an increase in urban green space's ET could be a useful way to improve the urban thermal environment and mitigate the UHI. Highlights: LULC has significant influence on air temperature and UHI. Green space has better cooling effect than urban landscape water. Air temperature is in negative linear relationship with vegetation coverage at night, but not in daytime. Tri-dimensional green biomass is an improvement for bi-dimensional vegetation coverage. There is a positive linear relationship between ET and the decrease rate of UHII.